2005
DOI: 10.1073/pnas.0409065102
|View full text |Cite
|
Sign up to set email alerts
|

Evasion of antibody neutralization in emerging severe acute respiratory syndrome coronaviruses

Abstract: Molecular characterization of the severe acute respiratory syndrome coronavirus has revealed genetic diversity among isolates. The spike (S) glycoprotein, the major target for vaccine and immune therapy, shows up to 17 substitutions in its 1,255-aa sequence; however, the biologic significance of these changes is unknown. Here, the functional effects of S mutations have been determined by analyzing their affinity for a viral receptor, human angiotensin-converting enzyme 2 (hACE-2), and their sensitivity to Ab n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
285
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 251 publications
(296 citation statements)
references
References 25 publications
9
285
2
Order By: Relevance
“…Second, although the S proteins of SARS-CoV isolated from humans during the 2003 epidemic were shown to bind to and use both human and palm-civet ACE2 efficiently, isolates from the 2004 minor outbreaks and those from palm civets used human ACE2 markedly less efficiently (11). Furthermore, substantial functional changes have been detected in the S proteins from a patient in late 2003 from Guangdong Province and from two palm civets, which depended less on the human ACE2 receptor and were markedly resistant to antibody inhibition (12). Third, although as many as 80% of the animals from markets in Guangzhou had significant levels of antibody to SARS-CoV, civets on farms were largely free from SARS-CoV infection (13).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Second, although the S proteins of SARS-CoV isolated from humans during the 2003 epidemic were shown to bind to and use both human and palm-civet ACE2 efficiently, isolates from the 2004 minor outbreaks and those from palm civets used human ACE2 markedly less efficiently (11). Furthermore, substantial functional changes have been detected in the S proteins from a patient in late 2003 from Guangdong Province and from two palm civets, which depended less on the human ACE2 receptor and were markedly resistant to antibody inhibition (12). Third, although as many as 80% of the animals from markets in Guangzhou had significant levels of antibody to SARS-CoV, civets on farms were largely free from SARS-CoV infection (13).…”
Section: Discussionmentioning
confidence: 89%
“…However, subsequent studies suggested that the civet may have served only as an amplification host for SARS-CoV and provided the environment for major genetic variations permitting efficient animal-tohuman and human-to-human transmissions (10)(11)(12)(13). Because civets are often mixed with different species in overcrowded conditions at markets, we conducted a surveillance study for CoV in noncaged animals from the wild areas of the Hong Kong Special Administrative Region (HKSAR).…”
mentioning
confidence: 99%
“…In SARS patients, apoptosis of cells of the lung epithelium has been observed, suggesting SARS-CoV-induced apoptosis to have a deleterious pathogenic role, leading to severe tissue damage (Yan et al, 2004). There are indications that apoptosis and the antiviral immune response may both contribute to the pathology in SARS patients (Yang et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies on HIV-1 showed that antibodies against some immunodominant epitopes in the HIV-1 envelope glycoprotein could enhance infection by heterologous HIV-1 strains (33). Most recently, Yang et al (6) demonstrated that the polyclonal and monoclonal antibodies against S protein of the late SARS-CoV (Urbani strain) could neutralize infection by the relevant late SARS-CoV strains. However, these antibodies enhanced infection by an early human SARS-CoV isolate (GD03T0013) and the civet SARS-CoV-like viruses.…”
Section: S Protein-based Vaccinesmentioning
confidence: 99%